Pendampingan Legalitas Nomor Induk Berusaha (NIB) Dalam Rangka Pengembangan UMKM Di Kelurahan Rontu Kota Bima - Kartin Aprianti; Indra Wani; ainun wulandari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
NIB Registration Assistance Activities in One of the areas targeted by the MBKM KKNT in 2022 is Rontu Village with an entrepreneurial and creative economy scheme. From the results of surveys and field observations, partner problems were found, such as that many people in the Rontu Sub-District do not have a Business Identification Number (NIB), which is important for MSMEs because it can lead to big profits and can attract other consumers and also generate higher sales. In addition, the community considers business licensing which was previously considered insignificant because the management is troublesome and not easy, however, MSMEs need business licensing to encourage business development, protect business locations and business competitiveness which is getting tougher in the current era. Therefore the purpose of this research is to provide assistance and understanding of the registration of Business Identification Numbers (NIB) in order to improve the MSME economy in the Rontu sub-district.